Syntheses, crystal structures and photoluminescent properties of new homoleptic and heteroleptic zinc(II) dithiocarbamato complexes. (8th January 2015) - Bharti, A.; Bharati, Pooja; Chaudhari, U.K.; Singh, A.; Kushawaha, S.K.; Singh, N.K.; Bharty, M.K.
Graphical abstract: Novel homoleptic dinuclear zinc(II) complex {[Zn2 (μ-ppdtc)2 (ppdtc)2 ] [Zn2 (μ2 -ppdtc)2 (ppdtc)2 ]} (1 ) and three new heteroleptic complexes [Zn(ppdtc)2 (bipy)] (2 ), [Zn(2-mppdtc)2 (py)] (3 ) and [Zn(mpdtc)2 (py)] (4 ) (ppdtc = phenyl piperazine dithiocarbamate, mppdtc = 2-methoxy phenyl piperazine dithiocarbamate and mpdtc = methyl piperazine dithiocarbamate) have been synthesized and characterized by various physicochemical techniques. Homoleptic complex {[Zn2 (μ-ppdtc)2 (ppdtc)2 ][Zn2 (μ2 -ppdtc)2 (ppdtc)2 ]} (1 ) contains two different asymmetric units of [Zn2 (μ-ppdtc)2 (ppdtc)2 ] (B ) and [Zn2 (μ2 -ppdtc)2 (ppdtc)2 ] (A ) in which each Zn(II) ion in one asymmetric dinuclear unit (B ) possess tetrahedral geometry, whereas in other asymmetric dinuclear unit (A ) both metal ions have five coordinate square pyramidal geometry. Complex [Zn(ppdtc)2 (bipy)] (2 ) has an octahedral geometry, coordinated through two nitrogen atoms of the bipyridyl and four sulfur atoms of the two units of the dithiocarbamato ligands. Complexes1 and2 are highly fluorescent in solution and emit light at 410 and 420 nm upon excitation at 330 and 360 nm wavelengths. Abstract: Novel homoleptic dinuclear zinc(II) complex {[Zn2 (μ-ppdtc)2 (ppdtc)2 ] [Zn2 (μ2 -ppdtc)2 (ppdtc)2 ]} (1 ) and three new heteroleptic complexes [Zn(ppdtc)2 (bipy)] (2 ), [Zn(2-mppdtc)2 (py)] (3 ) and [Zn(mpdtc)2 (py)] (4 ) (ppdtc = phenyl piperazine dithiocarbamate, mppdtc = 2-methoxy phenyl piperazine dithiocarbamate and mpdtc = methyl piperazine dithiocarbamate) have been synthesized and characterized by elemental analyses, IR, 1 H, 13 C NMR and X-ray crystallography. Homoleptic complex {[Zn2 (μ-ppdtc)2 (ppdtc)2 ][Zn2 (μ2 -ppdtc)2 (ppdtc)2 ]} (1 ) contains two different asymmetric units of [Zn2 (μ-ppdtc)2 (ppdtc)2 ] (B ) and [Zn2 (μ2 -ppdtc)2 (ppdtc)2 ] (A ) in which each Zn(II) ion in one asymmetric dinuclear unit (B ) possess tetrahedral geometry, whereas in other asymmetric dinuclear unit (A ) both metal ions have five coordinate square pyramidal geometry. Complex [Zn(ppdtc)2 (bipy)] (2 ) has an octahedral geometry, coordinated through two nitrogen atoms of the bipyridyl and four sulfur atoms of the two units of the dithiocarbamato ligands. Complexes [Zn(2-mppdtc)2 (py)] (3 ) and [Zn(mpdtc)2 (py)] (4 ) have distorted square pyramidal geometry, bonded through one pyridine nitrogen and four sulfur atoms of the two units of dithiocarbamato ligands. Complexes1 and2 are highly fluorescent in solution and emit light at 410 and 420 nm upon excitation at 330 and 360 nm wavelengths.